2022
DOI: 10.3389/fendo.2022.1060721
|View full text |Cite
|
Sign up to set email alerts
|

Oroxin B alleviates osteoarthritis through anti-inflammation and inhibition of PI3K/AKT/mTOR signaling pathway and enhancement of autophagy

Abstract: BackgroundOsteoarthritis (OA) is a common aging-related degenerative joint disease with chronic inflammation as its possible pathogenesis. Oroxin B (OB), a flavonoid isolated from traditional Chinese herbal medicine, possesses anti-inflammation properties which may be involved in regulating the pathogenesis of OA, but its mechanism has not been elucidated. Our study was the first to explore the potential chondroprotective effect and elucidate the underlying mechanism of OB in OA.MethodsIn vitro, primary mice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Autophagy is a host defense mechanism in mammalian cells that is not only closely related to cell metabolism, proliferation, and apoptosis, but also participates in the pathological process of various degenerative diseases [ 34 , 35 ]. However, proper activation of autophagy can prevent apoptosis and aging and may play a protective role in degenerative diseases [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is a host defense mechanism in mammalian cells that is not only closely related to cell metabolism, proliferation, and apoptosis, but also participates in the pathological process of various degenerative diseases [ 34 , 35 ]. However, proper activation of autophagy can prevent apoptosis and aging and may play a protective role in degenerative diseases [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“… 36 In addition, the PI3K-AKT-mTOR pathway is also an important inflammatory signaling pathway which associates with NF-κB signaling pathway, as AKT could trigger the activation of NF-κB signal and contribute to the production of inflammatory mediators. 37 , 38 Thus, in this study, we explored the role of MA in inflammatory signaling pathways in chondrocytes and revealed that MA was a protective agent against the progression of OA via suppressing the MAPK, NF-κB, and PI3K-AKT-mTOR signaling pathways and promoting the autophagy process in IL-1β-induced chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the PI3K/Akt pathway is closely related to osteoarthritis and that IL-1β can trigger a strong inflammatory response by activating a complex network of signalling pathways, in which PI3K/Akt signalling is closely intertwined with IL-1β-induced inflammation [ 37 ]. A large number of studies have shown that PI3K and Akt are rapidly phosphorylated under stimulation with IL-1β [ 38 , 39 ], suggesting that the PI3K/Akt pathway may mediate the initiation of the inflammatory response. PI3K inhibition is considered to be an anti-inflammatory therapeutic strategy [ 40 ].…”
Section: Discussionmentioning
confidence: 99%